Degradation of ammonia in an integrated anoxic-aerobic clarifier system - S. R. M. Kutty, Kutty (2018)

(untitled)
Wastewater effluent discharge in a large concentration of ammonia, nitrate and phosphorus lead to eutrophication the river. Eutrophication is a serious environmental issue that threatens the fishes and aquatic plants. To prevent this from happening, ammonia produced in sewage treatment plant (STP) and raw wastewater removal is achieved during nitrification by having an extended aeration while nitrate removal is achieved during denitrification in anoxic tank. In this study, a pilot plant of integrated suspended growth system (i-SGS) reactor was used to achieve simultaneous removal of ammonia and nitrate. The reactor has three main compartments which are anoxic chamber, aeration camber, and clarifier and operated at a constant flow rate of 720 L/d and fixed sludge retention time (SRT) of 40 days. The return activated sludge (RAS) time was set to once every 10 minutes for 5 minutes while the internal recirculation (IR) time is once every 16 minutes for 5 minutes. The wastewater quality parameters, namely chemical oxygen demand (COD), ammonia, and nitrate were measured to determine and evaluate the removal efficiency. In addition phosphorus was measured to ensure the effluent standard meet the C:N:P ratio requirement. Samples from four sampling points were taken in triplicate for analyze of all parameters.